1995
DOI: 10.1016/s0022-5223(95)70432-9
|View full text |Cite
|
Sign up to set email alerts
|

Surgery for congenital mitral valve disease in the first year of life

Abstract: Between 1980 and 1993, 20 patients less than 1 year of age underwent operations for congenital mitral valve disease. Ten patients had congenital mitral incompetence and 10 had congenital mitral stenosis. Mean age was 6.6 +/- 3.4 months and mean weight was 5.6 +/- 1.5 kg. Atrioventricular canal defects, univentricular heart, class III/IV hypoplastic left heart syndrome, discordant atrioventricular and ventriculoarterial connections, and acquired mitral valve disease were excluded. Indications for operation were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0
1

Year Published

1999
1999
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(50 citation statements)
references
References 28 publications
2
47
0
1
Order By: Relevance
“…Upon transfer, 2D and Doppler echo examination revealed severely restricted mobility and opening of the MV leaflets with concomitant LV inflow obstruction on color Doppler. Two closely spaced papillary muscles with short chordal attachments to the mitral leaflets were noted, conforming to the features described as typical symmetric hypoplastic mitral valve [5]. The mitral annulus measured 13 mm in diameter.…”
Section: Case Reportsupporting
confidence: 75%
See 1 more Smart Citation
“…Upon transfer, 2D and Doppler echo examination revealed severely restricted mobility and opening of the MV leaflets with concomitant LV inflow obstruction on color Doppler. Two closely spaced papillary muscles with short chordal attachments to the mitral leaflets were noted, conforming to the features described as typical symmetric hypoplastic mitral valve [5]. The mitral annulus measured 13 mm in diameter.…”
Section: Case Reportsupporting
confidence: 75%
“…Mitral valve repair procedures such as surgical commisurotomy and valve replacement in children carry inordinately high risks, especially in infants [7], although among the more recent series Uva et al [5] reported zero operative mortality for congenital mitral valve anomalies operated during infancy. Despite improved operative mortality, however, late morbidity continues to limit the success of surgical management in this disease.…”
Section: Discussionmentioning
confidence: 99%
“…Comparing practices in different places has provided crucial insights, from Semmelweis's discovery of antisepsis to more recent evidence about the optimal age for surgery to repair congenital mitral valve disease. 21 However, controlled studies of this type are entirely different from single site investigations called down on organisations by regulatory bodies. In Mid Staffordshire "concerns about mortality" prompted first the HCC investigation, 22 then two reviews commissioned by the Department of Health, 23 24 and finally an independent inquiry set up by the secretary of state for health.…”
Section: Defining the Principled Use Of Mortality Ratesmentioning
confidence: 99%
“…In Carpentier's series 3 , the age of the congenital mitral insufficiency group was 6.1±3.2 years and in the congenital mitral stenosis group 5.1±3.2 years. In the report by Uva and colleagues 11 , from MarieLannelongue Hospital, the congenital mitral insufficiency group was 7.4±2.7 months old, and the congenital mitral stenosis group was 5.8±3.9 months old. The factors that explain the lower age of the congenital mitral stenosis patients at the time of surgery are 1) the stenotic lesion is less tolerated than the insufficiency; 2) the association with higher and more severe intracardiac anomalies; 3) the abnormalities of the subvalvular apparatus are more frequent in these patients.…”
Section: Discussionmentioning
confidence: 89%